Iranian Advanced EFL Learners’ Perception of Criteria-Referenced Self-and-Peer Assessment: Benefits and Challenges - Behrooz Azabdaftari; sanaz sanaz sabermoghaddam; Zohreh Seifoori (Journal of Applied Linguistics)
Self-assessment, a form of alternative assessment focusing on learner-centered curricula, autonomy, and needs analysis, has gained prominence recently. Via individual and cooperative self-assessment, EFL learners notice and apply the established standards and criteria that would decide on the accuracy and fluency of their productions, particularly in challenging areas like writing that require detailed forms of assessment. Here, learners’ capacity to self-assess and peer-assess their writings could contribute to their developmental functions. The objective of this study was to explore a specific number of Iranian EFL learners’ perceptions of criteria-referenced self-and-peer assessment in writing through a mixed-method survey. Sixty EFL learners were asked to answer a questionnaire on self-and-peer assessment. Additionally, 15 learners were requested to answer semi-structured interview questions to express their perceptions toward criteria-referenced self-and-peer assessment. For the quantitative phase of the study, a self- and peer-assessment questionnaire developed by Cornelius and Kinghorn (2014) was utilized. The questionnaire's reliability was assessed using Cronbach’s alpha, and content validity was confirmed. For the qualitative phase of the study, the researcher developed and conducted a semi-structured interview with five open-ended questions with validated content. The data related to the quantitative and qualitative phases were analyzed through descriptive statistics including the frequency percentage and content analysis methods, respectively. Results revealed learners had positive perceptions towards criteria-referenced self-and peer assessment in language classes. The findings offer beneficial implications for EFL teachers, learners, test developers, and administrators.